Synthesis, Characterization and Antimicrobial Activity of Substituted Phenyl-5-(8-hydroxy quinolinol-5-yl) Pyrazolines - Patel, V.G.; Patel, B.K.; Patel, J.C. (Asian Journal of Chemistry, 2016)
Various chalcone derivatives (3a–e) were prepared by the well known Claisen-Schmidt condensation reaction of 8-hydroxy-5-quinoline carboxaldehyde (1) and different substituted acetophenones (2a–e). The chlicones (3a–e) were then reacted with hydrazine in aqueous alkali and yielded 3-substituted phenyl 5-(8-hydroxy quinolinol-5-yl) pyrazolines (4a–e). All the pyrazoline derivatives were characterized by elemental analysis, spectral studies and antimicrobial activities. One of the pyrazolines (4b) was then treated with transition metal salts and afforded metal chelates of 4b. All the metal chelates were characterized by metal : ligand (M : L) ratio, magnetic moment, reflectance spectra and antimicrobial activities.